1998
DOI: 10.1021/jp9731967
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Preparation of Platinum Nanocrystallites with Size Selectivity on Basal Plane Oriented Graphite Surfaces

Abstract: Platinum nanocrystals were deposited on basal plane oriented graphite surfaces from dilute (1.0 mM) PtCl 6 2-containing electrolytes using a pulsed potentiostatic method. The deposition of platinum nanocrystals occurred via an instantaneous nucleation and diffusion-limited growth mechanism which resulted in narrow particle size distributions (relative standard deviation <35%) for mean crystallite diameters smaller than 40 Å. The number of particles per unit area on these surfaces was 10 9 -10 10 cm -2 . Noncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
327
1
9

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(366 citation statements)
references
References 37 publications
(58 reference statements)
22
327
1
9
Order By: Relevance
“…Noncontact atomic force microscope (NC-AFM) images of a graphite surface following the deposition of 0.039 monolayer of platinum, for example, are shown in Figure 2a. 19 Platinum nanoparticles having a mean diameter of 52 Å are seen on a graphite surface in this image. The image of Figure 2a also shows that platinum nanoparticles have nucleated both at defect sites such as step edges, and on atomically smooth terraces.…”
Section: Electrodeposition Of Size-monodisperse Metal Nanoparticlesmentioning
confidence: 78%
“…Noncontact atomic force microscope (NC-AFM) images of a graphite surface following the deposition of 0.039 monolayer of platinum, for example, are shown in Figure 2a. 19 Platinum nanoparticles having a mean diameter of 52 Å are seen on a graphite surface in this image. The image of Figure 2a also shows that platinum nanoparticles have nucleated both at defect sites such as step edges, and on atomically smooth terraces.…”
Section: Electrodeposition Of Size-monodisperse Metal Nanoparticlesmentioning
confidence: 78%
“…[20][21][22][23] Electrodeposition has also been used for synthesis of metal nanocrystallites on carbon based substrates such as highly oriented pyrolytic graphite (HOPG). [24][25][26] Finot et al have reported synthesis of gold nanocrystals by applying a potential step to GC as the substrate for a specific time (5 s) using dilute solutions of KAuCl 4 (1.0 × 10 -5 -2.0 × 10 -4 M) in H 2 SO 4 (0.5 M) and applying different overpotentials to investigate the effect of concentrations and potential on particle size. 27,28 The effects of substrates, additives (iodide ions and cysteine) and deposition times on the size, morphology and crystallographic orientation of gold have been studied by El-Deab et al by using GC, HOPG and gold electrodes in acidic medium containing gold salt.…”
Section: Introductionmentioning
confidence: 99%
“…13,24 The driving force for this process has been suggested to be related to the presence of incompletely oxidized functionalities existing at terraces and kink sites on freshly cleaved HOPG surface. 13 Here, we immersed an as-cleaved HOPG into 0.5 M H 2 SO 4 containing electrochemically dissolved Pt ions to evaluate the chemical interaction between dissolved Pt ions and HOPG. As seen in Figure 2, individual Pt nanoparticles can be observed at the edge sites on the HOPG surface, which indicates that dissolved Pt ions have properties similar to PtCl 6 2− .…”
Section: Resultsmentioning
confidence: 99%
“…The individual Pt nanoparticles have an average diameter of 10-20 nm with height of about 1.5-2.5 nm, similar in geometry to Pt nanoparticles reduced on the edge sites of HOPG from PtCl 6 2− . 13,24 It is assumed that the dissolved Pt ions are spontaneously reduced by the incompletely oxidized functionalities at the edge sites, analogous to the case for PtCl 6 2− . 13 The characteristic plate-like morphology may come from the high mobility of as-reduced Pt on the HOPG surface leading to a two-dimensional growth.…”
Section: Resultsmentioning
confidence: 99%